Bahasa Inggris - Aghasi Hana Faradila; Rossalina Adi Wijayanti; Novita Nuraini; Riskha Dora Candra Dewi (Politeknik Negeri Jember, 2023)
The incomplete filling of medical records affects the quality of medical record services and has an impact on the discontinuity of health services provided to patient. Based on the result of observations at the Puskesmas Babadan , it is known that there was an incompleteness of outpatient medical records with a percentage of 27,3% with the number of medical records that are not completely filled as many as 44 from 161 outpatient medical records. This study aims to analyze the factors causing the incompleteness of outpatient medical records at the Puskesmas Babadan by priorotizing problems using the Urgency, Seriousness, Growth (USG) method and improvement efforts through brainstorming. The results found in this study are based on motivation variables namely the absence of rewards and punishments given to officers, based on the opportunity variables namely that there is no Standard Operating Procedures (SOP) that regulates the completeness of filling out medical records and officers involved in filling out outpatient medical records have never received training on the completeness of filling out medical records, based on the ability variables, namely the ability of education, experience and medical staff to assist in filling out outpatient medical records. The absence of Standard Operating Procedures (SOP) which is the cause of incomplete filling of outpatient medical records. The effort to fix the problem is by making clear Standard Operating Procedures (SOP) regarding the completeness of filling out medical records in accordance with applicable medical record service standars.